PENGUATAN DIMENSI KEBHINEKAAN GLOBAL PROFIL PELAJAR PANCASILA MELALUI AKTIVITAS KEAGAMAAN DI SEKOLAH DASAR - Apriliana, Riska Ayu; Supriyadi, Supriyadi (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to describe religious activities to strengthen global diversity character in accordance with the Pancasila Student Profile at SD Islam Chusnaini Sidoarjo. The research employed a qualitative approach with a descriptive method. The subjects were the vice-principal and teachers actively involved in religious activities at the school. Data were collected through in-depth interviews, observations, and documentation. Data analysis was conducted using Miles and Huberman’s interactive model, including data condensation, data display, and drawing conclusions. The results indicate that the school implements religious activities to foster global diversity character through practices such as morning motivation, congregational prayers in the classroom, recitation activities, rotating morning prayers, celebrating religious holidays, and creating posters promoting tolerance and brotherhood. These activities effectively strengthen the Pancasila Student Profile and contribute to the development of students’ global diversity character.